Penerapan Strategi Pembelajaran Stad Untuk Meningkatkan Minat dan Kemampuan Pemecahan Masalah Matematika Siswa Kelas V SDN Jeruk 1 Kecamatan Miri Tahun 2015/2016 - Anisa, Nur Laila, Drs. Saring Marsudi, SH. M.Pd (2016)
The aim of this research is to improve interest by implementing STAD learning strategy in class V SDN Jeruk 1 Kecamatan Miri 2015/2016 academic year. And to improve the ability to solve the problems of FPB and KPK to implement the strategy of STAD in class V SDN Jeruk 1 Kecamatan Miri 2015/2016 academic year. Based on the results of Class Action Research conducted in the learning of mathematics in two cycles can be concluded that with the implementation of STAD learning strategies can increase the interest and ability to solve a math problem in class V students of SD Negeri Jeruk 1 Miri District of Sragen 2015/2016 Academic Year. This was evident at pra-cycle student interests only 52.25%. In the first cycle student's interest increased to 63.25%. While on the second cycle the student's interest increased to 82.75%. After the implementation of the action in the second cycle, the classical completeness of students has increased. If the classical completeness pra-cycle only 20%, then the first cycle increased to 48%. In the second cycle classical completeness increased again to 88%. Thus the implementation of STAD learning strategies can be implemented to increase the interest and ability to solve a math problem in class V students of SD Negeri Jeruk 1 Sragen 2015/2016 Academic Year.